2016
DOI: 10.3402/ejpt.v7.30933
|View full text |Cite
|
Sign up to set email alerts
|

How to support staff deploying on overseas humanitarian work: a qualitative analysis of responder views about the 2014/15 West African Ebola outbreak

Abstract: BackgroundResponding to health crises overseas can be both rewarding and distressing for staff involved.ObjectiveWe interviewed UK staff involved in the 2014/15 Ebola response to identify experiences that positively or negatively affected them.MethodWe conducted qualitative telephone interviews with 30 Public Health England (PHE) staff and 21 non-governmental organisation (NGO) staff who had deployed to West Africa.ResultsThe main motivations for deploying were for moral reasons and personal development. Famil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
77
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 51 publications
(79 citation statements)
references
References 21 publications
2
77
0
Order By: Relevance
“…Perceived threat or lack of safety have also been shown to be predictors of poor wellbeing in disaster responders and emergency personnel 39,40 and more recently were noted as important concerns in a qualitative study of staff deployed to Africa during the 2014/15 Ebola outbreak 41 . Again, specialised training may help to minimise the amount of risk felt by employees and thus lead to more positive outcomes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Perceived threat or lack of safety have also been shown to be predictors of poor wellbeing in disaster responders and emergency personnel 39,40 and more recently were noted as important concerns in a qualitative study of staff deployed to Africa during the 2014/15 Ebola outbreak 41 . Again, specialised training may help to minimise the amount of risk felt by employees and thus lead to more positive outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…through loss of housing/income or reduced contact with family 40,44 . However, there has also been much research suggesting that humanitarian work can have a positive impact on life: qualitative research involving relief workers and healthcare workers who have responded to disasters and disease outbreaks has suggested that 13 they experience positive effects such as personal growth, a greater appreciation for life and a sense of achievement 41,45 . It may be useful for preparatory training packages and interventions to encourage healthcare workers to focus on the potential positive impact of their work or to consider coping strategies which may help them to see the positive effects of working in a crisis.…”
Section: Discussionmentioning
confidence: 99%
“…They also often have catastrophic appraisals of any physical symptoms experienced during the quar antine period. This fear is a common occurrence for people exposed to a worrying infectious disease, 41 and might be exacerbated by the often inadequate information participants reported receiving from public health officials leaving them unclear of the nature of the risks they faced and why they were being quarantined at all. Ensuring that those under quarantine have a good understanding of the disease in question, and the reasons for quarantine, should be a priority.…”
Section: Give People As Much Information As Possiblementioning
confidence: 99%
“…[12] With focus squarely on containing the outbreak and dealing with the immensity of the task at hand, many fail to notice the associated emotional and psychological toll. [34] Posttraumatic stress disorder (PTSD) is defined by Diagnostic and Statistical Manual of Mental Disorders, 5 th edition as a specified constellation of emotional and behavioral responses to traumatic events.…”
Section: Introductionmentioning
confidence: 99%